ANALISIS KEBIJAKAN KREDIT TERHADAP PENGEMBANGAN USAHA PERIKANAN NELAYAN TRADISIONAL DI KABUPATEN TOJO UNA-UNA - Dewi Nur Asih (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Credit aid programs can be used as a mean to improve the contribution of fishery sector. The impact of such credit on traditional fisheries was determined on the fishery productivity and their traditional fisherman income in Sulawesi Tengah Province. The research result showed that the credit was needed as an additional capital for the fishery sustainability. With such credit, the productivity of the fisheries increased as shown by sufficiently high incremental benefit which the fishermen achieved.  The  credit  also  affected  the  fisherman  household  in  making  decision  related  to  such  economic  behaviors  as productivity  activities,  working  time,  income  and  expenditure.  Thus  these  behaviors  were  analyzed  using  an  econometric approach with a simultaneous equation.